Does gender matter in online courses? A view through the lens of the community of inquiry - Cho, Moon-Heum; Lim, Seongmi; Lim, Jieun; Kim, Onjoo (Australasian Journal of Educational Technology, 2022)
The purpose of this study was to investigate whether gender differences exist in relationships between the three presences – teaching, cognitive and social – in the community of inquiry (CoI) model and online students’ learning experiences measured with perceived learning and course satisfaction. Participants were 657 undergraduates taking online courses at a university in South Korea. Results showed significant differences in sub-elements of cognitive and social presence by gender. In addition, regression analyses revealed that sub-elements of the CoI predicted online students’ perceived learning and course satisfaction differently by gender. A discussion explains gender differences in online courses in South Korea in which a prerecorded video was the principal modality of learning. Finally, practical implications to enhance diverse students’ success are proposed from the perspective of the CoI model. Implications for practice or policy: Despite the development of the CoI specifically for a discussion-based online course, it can still be used to predict students’ learning experiences in video-based online learning. Considering gender difference when designing and developing an online course may enhance student learning experiences in online learning. Changing the way the videos are created may contribute to enhancing the three presences in the CoI model, which essentially improve online students’ learning experiences.